Corneal curvature radius in myopia of schoolchildren versus adult myopia - Jonas, Jost B.; Panda-Jonas, Songhomitra (Cornea, 2016)
Purpose: To assess whether anterior corneal curvature radius (CCR) is associated with the increased prevalence of myopia in Asia. - Methods: The investigation included the adult populations of the Central India Eye and Medical Study (CIEMS; 4711 adults) and Beijing Eye Study (BES; 3468 adults) and the children and teenager populations of the Shandong Children Eye Study (6026 children; age: 9.7 ± 3.3 years; range: 4-18 years) and Beijing Pediatric Eye Study (681 children; age: 7.7 ± 1.6 years; range: 5-13 years). - Results: In both adult study populations, CCR was not significantly (BES: P = 0.60; CIEMS: P = 0.14) associated with the level of education. In highly myopic subgroups, longer CCR was associated with a lower educational level [CIEMS: P = 0.04; standardized regression coefficient β = −0.23; nonstandardized regression coefficient B: −0.06; 95% confidence interval (CI), −0.11 to 0.01] or showed a tendency toward a lower educational level (BES: P = 0.09; β = −0.25; B: −0.06; 95% CI, −0.12 to 0.01). In the young study populations, longer CCR was significantly associated with parameters indicating a lower educational level, such as lower educational level of father (P = 0.001; β: −0.04; B: −0.01; 95% CI, −0.02 to −0.01) and mother (P = 0.0.02; β: −0.14; B: −0.05; 95% CI, −0.09 to −0.01) and more time spent outdoors (P = 0.001; β: 0.15; B: 0.05; 95% CI, 0.02 to 0.07) and less time spent indoors (P < 0.001; β: −0.15; B: −0.04; 95% CI, −0.06 to −0.02). In all study populations, longer CCR was significantly correlated (multivariate analysis) with longer axial length and lower prevalence of high myopia. - Conclusions: Adult study populations and schoolchildren populations did not differ in the associations of longer CCR with parameters indicating a lower educational level, longer axial length, and lower prevalence of high myopia. CCR was not useful for the differentiation between high myopia in schoolchildren and high pathological myopia in adults.
Gesehen am 10.07.2019